قواعد تفسير شرط الواقف كنص الشارع: دراسة تأصيلية تطبيقية - الشايب، فراس عبدالحميد أحمد (جامعة آل البيت, 2021)
تبرز أهمية موضوع البحث في إظهار أهم القواعد الفقهية والأصولية التي استلهمها الفقهاء كوسيلة لحل التنازع في تفسير عبارات الواقفين وشروطهم، وما يترتب عليها، فهو محاولة لإظهار هذا الدور للقواعد الفقهية والأصولية، ويدور موضوع البحث حول مسألتين: تتمثل الأولى منهما في بيان معنى قاعدة شرط الواقف كنص الشارع: أما الثانية فمن خلال معرفة أثر هذه القواعد في تفسير شروط الواقفين، كل ذلك من خلال المنهجين: الوصفي، والتحليلي. وخلص الباحث في نهاية بحثه إلى مجموعة من النتائج، منها: أن القاعدة الفقهية على الرغم من تميزها عن القاعدة الأصولية من بعض الوجوه إلا أن كلا منهما لها دورها في تفسير عبارات الشرط، ويوصي الباحث بضرورة اهتمام دائرة قاضي القضاة بتولية قضاة في المحاكم الشرعية للنظر في أحكام الوقف بشكل خاص، ممن لديهم المعرفة الكاملة بأحكام الأوقاف في المذاهب الفقهية الأربعة.
The importance of the topic of the research is highlighted in showing the most important jurisprudential and fundamentalist rules that were inspired by the jurists as a means to resolve the conflict in the interpretation of the terms and conditions of Al-Waqefeen, and the consequences of it, it is an attempt to show this role of the jurisprudential and fundamentalist rules, and the topic of research revolves around two issues: The first of them is to clarify the meaning of the rule of the condition of the Al-Waqef the Al- Sharea text, The second lies in the rules that the judge uses to reach the lifting of ambiguity when explaining the conditions of Al-Waqefeen, all through the two methodologies: The descriptive, and the analytical. The researcher concluded at the end of his research to a set of results, including: that the jurisprudential rule, despite its distinction from the fundamentalist rule in some ways, but each of them has its role in interpreting the terms of the condition, The researcher recommends that the supreme judge department should pay attention to the appointment of special judges in Sharia courts to consider waqf rulings who have full knowledge of the provisions and jurisprudential differences in endowment rulings in the four schools of jurisprudence.
Keywords: أحكام الوقف -- القواعد الفقهية -- شروط الواقفون -- القواعد الأصولية